In vitro transcription of HIV-1 RNA for standard RNA (Faculty of Medicine Universitas Indonesia, 2011)
Background: The quantitative assays are important tests in the management of patients with HIV-1/AIDS. The important step in developing the assay is the availability of the standard HIV-1 RNA. For this purpose, we optimized in vitro HIV-1 RNA transcription to produce the standard HIV-1 RNA. Methods: The HIV-1 DNA was amplified from pNL43 by PCR using a primer pair that was specific for conserved region of HIV-1 Gag gene. The PCR product was further cloned into pBluescript II KS. The recombinant plasmid was restricted with EcoRI enzyme. Then, the linearized plasmid was used as template for RNA transcription. RT-PCR and PCR were performed simultaneously for confirmation of synthesized RNA fragment. Results: A 115 bp DNA of HIV-1 Gag gene has been cloned into pBluescript II SK with the exact true orientation. TheÂ reaction of the RNA transcription was also successfully performed. The RNA transcripts have been confirmed and showed the accuracy of the transcripts. Conclusion: We successfuly constructed the recombinant plasmid containing a conserved region of HIV-1 Gag gene, and the HIV-1 RNA has been transcribed in vitro as well. (Med J Indones. 2011; 20:185-9)